Polyphosphate delays fibrin polymerisation and alters the mechanical properties of the fibrin network - Whyte, Claire S.; Chernysh, Irina N.; Domingues, Marco M.; Connell, Simon; Weisel, John W.; Ariens, Robert A. S.; Mutch, Nicola J. (Thrombosis and Haemostasis, 2016)
Polyphosphate (polyP) binds to fibrin(ogen) and alters fibrin structure, generating a heterogeneous network composed of ‘knots’ interspersed by large pores. Here we show platelet-derived polyP elicits similar structural changes in fibrin and examine the mechanism by which polyP alters fibrin structure. Polymerisation of fibrinogen with thrombin and CaCl2 was studied using spinning disk confocal (SDC) microscopy. PolyP delayed fibrin polymerisation generating shorter protofibrils emanating from a nucleus-type structure. Consistent with this, cascade blue-polyP accumulated in fibrin ‘knots’. Protofibril formation was visualized by atomic force microscopy (AFM) ± polyP. In the presence of polyP abundant monomers of longer length were visualised by AFM, suggesting that polyP binds to monomeric fibrin. Shorter oligomers form in the presence of polyP, consistent with the stunted protofibrils visualised by SDC microscopy. We examined whether these structural changes induced by polyP alter fibrin’s viscoelastic properties by rheometry. PolyP reduced the stiffness (G’) and ability of the fibrin network to deform plastically G”, but to different extents. Consequently, the relative plastic component (loss tangent (G”/G’)) was 61 % higher implying that networks containing polyP are less stiff and more plastic. Local rheological measurements, performed using magnetic tweezers, indicate that the fibrin dense knots are stiffer and more plastic, reflecting the heterogeneity of the network. Our data show that polyP impedes fibrin polymerisation, stunting protofibril growth producing ‘knotted’ regions, which are rich in fibrin and polyP. Consequently, the mechanical properties of the fibrin network are altered resulting in clots with overall reduced stiffness and increased ability to deform plastically.Supplementary Material to this article is available online at www.thrombosis-online.com.
Keywords: Fibrin(ogen); polyphosphate; polymerisation